(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2025)
This review highlights the relevance of the publication of the book "Scenic Makeup - Techniques, Processes and Procedures”, by Márcio Desideri, both for the field of character design and creation of scenic visuality, and for the area of ​​makeup more broadly. The work is part of a body of work that involves years of research and professional practice, filling a gap in publications in the field, which until now were aimed at a non-specialized audience and, therefore, lacked the demand for specific theoretical and technical depth. With accessible language and a keen eye for recovering the historical relevance of this artistic field, Márcio provides the reader with an incursion into the universe of makeup, highlighting its fundamentals, and then presenting various techniques and procedures, work equipment, sketches for reproduction, among others. It is a precious and dedicated work that reinforces the importance of in-depth training for professionals in the field and arrives on the market to complement courses, training, and professional development programs.